2022
DOI: 10.1109/tie.2021.3060635
|View full text |Cite
|
Sign up to set email alerts
|

Triaxial Fast Tool Servo Using Hybrid Electromagnetic–Piezoelectric Actuation for Diamond Turning

Abstract: A high-performance tri-axial fast tool servo (FTS) with the hybrid electromagnetic-piezoelectric actuation and the hybrid parallel-serial-kinematic structure is reported. Featuring the balanced and uniform actuation, a novel axis-symmetric linearized reluctance actuator is proposed to generate the planar motion in parallel, and the piezo-actuated vertical motion is then serially carried by the planar motion within a limited space. Verified by the finite element analysis, a two-stage design strategy is develope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…As shown in Figure 7a, via a four-axis ultra-precision lathe (Moore Nanotech 350FG, USA) with self-designed tri-axial FTS [30], one machining experiment was performed to verify the validity of the proposed method. The loopshaping tuned PID controller with a feedforward compensator and a damping controller are employed in FTS to improve the trajectory tracking accuracy.…”
Section: Experiments Results and Discussionmentioning
confidence: 99%
“…As shown in Figure 7a, via a four-axis ultra-precision lathe (Moore Nanotech 350FG, USA) with self-designed tri-axial FTS [30], one machining experiment was performed to verify the validity of the proposed method. The loopshaping tuned PID controller with a feedforward compensator and a damping controller are employed in FTS to improve the trajectory tracking accuracy.…”
Section: Experiments Results and Discussionmentioning
confidence: 99%
“…Zhu, Z.H. et al [ 17 ] reported high-performance triaxial FTS with hybrid electromagnetic–piezoelectric actuation and a hybrid parallel–serial-kinematic structure. To generate the planar motion as well as to carry the piezoactuated vertical motion, a novel axis-symmetric linearized reluctance actuator (AS-LRA) was proposed.…”
Section: Introductionmentioning
confidence: 99%
“…FTS uses a high bandwidth actuator to drive the diamond tool to generate linear reciprocating fast servo motion, and combines spindle rotation motion and tool feed motion to cut the optical free-form surface [10]. Several actuators commonly used in FTS include piezoelectric actuator [11], Lorentz force actuator [12] and Maxwell electromagnetic actuator [13]. Piezoelectric actuator has the superiorities of high precision, high stiffness, large output force, and is relatively more widely used in FTS [14].…”
Section: Introductionmentioning
confidence: 99%